Edexcel AS & A level politics - Colclough, Andrew; Goodlad, Graham; Laycock, Samantha; Levinson, Ian; Mitchell, Andrew; Schindler, Kathy; Tomes, Adam (Pearson, 2017)
This student book with e-book is specifically designed for the Edexcel AS and A level politics 2017 specifications, giving you comprehensive coverage of the qualification content and great support for the new assessments - in both print and digital formats. It concludes support for all the Components: UK Politics and Core Political Ideas, UK Government and Non-Core Political Ideas, Comparative Politics (US and Global). Includes online access to an ActiveBook. An online version of the 2017 General Election case study is also available.